2015
DOI: 10.15403/jgld.2014.1121.qix
|View full text |Cite
|
Sign up to set email alerts
|

Association between Portal Vein Thrombosis and Survival of Liver Transplant Recipients: a Systematic Review and Meta-analysis of Observational Studies

Abstract: Background & Aims: Portal vein thrombosis (PVT) increases the technical complexity of liver transplantation (LT). This systematic review and meta-analysis aim to analyze the association of pre-LT PVT with the overall survival after LT.Methods. PubMed, EMBASE, and Cochrane library databases were used to search for papers related to the association between pre-LT PVT and survival of LT recipients. The differences in the survival rates between the LT recipients with and without pre-LT PVT were expressed as od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 42 publications
2
45
0
3
Order By: Relevance
“…In the study by Pécora et al, the patients with PVT grade I presented a 5 y survival rate identical to controls (86%); but patients with degrees II, III and IV had lower survivals [1] as shown in our series. Qi et al, showed that the recipients with preoperative PVT, especially with complete thrombosis, had no statistically significant difference in perioperative or five year survival rate than patients without PVT [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Pécora et al, the patients with PVT grade I presented a 5 y survival rate identical to controls (86%); but patients with degrees II, III and IV had lower survivals [1] as shown in our series. Qi et al, showed that the recipients with preoperative PVT, especially with complete thrombosis, had no statistically significant difference in perioperative or five year survival rate than patients without PVT [30].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, overall morbidity and mortality in LT recipients of are not influenced by the presence of PVT [ 83 ]. However, in a recent meta-analysis [ 84 ], it was demonstrated that LT recipients with pre-LT PVT had a significantly lower 1-year survival rate compared to those without (odds ratio [OR] 0.733, 95% confidence interval [CI] 0.621-0.865). In the subgroup with complete PVT, the prognostic value was more pronounced (OR 0.503, 95%CI 0.295-0.858), but the impact of PVT on the 5-year survival was not significant.…”
Section: Pvt and Ltmentioning
confidence: 99%
“…Portal venous system thrombosis (PVST) refers to the formation of a thrombus within the intrahepatic portal vein branches, main portal vein (MPV), splenic vein (SV), and superior mesenteric vein (SMV) [ 1 , 2 ]. Given the relatively high prevalence and negative prognostic impact of PVST in liver cirrhosis [ 3 6 ], understanding the risk factors of PVST is important to optimize the prevention strategy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%